First-mover advantages - Lieberman, Marvin B.; Montgomery, David B. (Strategic Management Journal, 1988)
This article surveys the theoretical and empirical literature on mechanisms that confer advantages and disadvantages on first-mover firms. Major conceptual issues are addressed, and recommendations are given for future research. Managerial implications are also discussed.